2003
DOI: 10.1103/physrevlett.90.016107
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Local Optical Properties: Near-Field Polarimetry of Photonic Block Copolymer Morphology

Abstract: Ultrahigh molecular weight polystyrene-b-polyisoprene block copolymers (BCs), noted for their photonic behavior, were imaged using transmission near-field scanning optical microscopy (NSOM) and NSOM polarimetry. Our improved scheme for polarization modulation (PM) polarimetry, which accounts for optical anisotropies of the NSOM aperture probe, enables mapping of the local diattenuation and birefringence (with separately aligned diattenuating and fast axes) in these specimens with subdiffraction limited resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…It is found that without knowing properties of a near-field optical fiber probe and compensating for its polarization effects, the signal will be easily contaminated. However, the algorithms developed in [4][5][6][7] were overly complex for practical use.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is found that without knowing properties of a near-field optical fiber probe and compensating for its polarization effects, the signal will be easily contaminated. However, the algorithms developed in [4][5][6][7] were overly complex for practical use.…”
Section: Introductionmentioning
confidence: 98%
“…Fasolka et al [4] and Goldner et al [5,6] used a photo-elastic modulator (PEM) and a Fourier analysis scheme to measure the principal axis angle, retardance, diattenuation axis angle, and diattenuation of the local optical properties of photonic block copolymers and polystyrene-b-polyisoprene block copolymers, respectively. Also, Campillo and Hsu [7] measured the birefringence and diattenuation properties of SiN membranes using a NSOM technique in which the polarization of the input light was adjusted using a PEM and the detected signal was processed using a Fourier analysis scheme.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Versatility of the NSOM is highlighted by reports investigating varied phenomenon such as photonic block copolymer morphology, 17 fluorescence imaging of biological samples, 15 imaging of second-harmonic generation in ZnO nanowires, 18 observation of local ferroelectric phase transitions, 19 and among many others. With significant technological advances in NSOM tip fabrication and with major advances in instrumentation, NSOM will continue to serve as a valuable tool to probe optical properties of nanostructures.…”
Section: Introductionmentioning
confidence: 98%
“…[25,26] These investigations thus call for a high-resolution chemically specific imaging technique to visualize the spatial and chemical composition of the polymer. [27][28][29] Here, a nanoscale surface analysis and identification of the domains formed by phase separation in thin films was achieved, choosing poly(styrene-b-2-vinylpyridine) (PS-b-P2VP) and poly(styrene-b-ethyleneoxide) (PS-b-PEO) as model systems. ), contrast is obtained due to spectral differences between the CÀH stretching vibrational resonances of the respective polymer constituents.…”
Section: Introductionmentioning
confidence: 99%